Impending central retinal vein occlusion and granulomatous uveitis in a patient with Satoyoshi syndrome. Issue 11 (17th March 2023) - Saima, Yoshinari; Tanaka, Yoshiaki; Kakehashi, Akihiro; Kaburaki, Toshikatsu
Abstract : Rationale: Satoyoshi syndrome is a rare systemic autoimmune disease that presents with painful muscle spasms. We report a case of impending central retinal vein occlusion (CRVO) secondary to granulomatous pan-uveitis in a 32-year-old woman with Satoyoshi syndrome. Patient concerns: At the age of 7 years, she developed generalized hair loss and painful spasms and was diagnosed with Satoyoshi syndrome. Her current symptoms included sudden metamorphopsia and decreased visual acuity in the left eye. She visited our hospital with extensive intraretinal hemorrhage (including the macula), meandering of the retinal veins, and swelling of the optic disc. Fluorescence fundus angiography demonstrated hyper fluorescence of the optic disc and leakage from the retinal veins, suggesting CRVO associated with optic papillitis and segmental periphlebitis. Diagnoses: In the left eye, there were 2 + cells in the anterior chamber and 1 + in the anterior vitreous. Interventions: We increased the existing dose of prednisolone for the treatment of uveitis and started her on oral aspirin and kallidinogenase for CRVO. Outcomes: The impending CRVO gradually subsided, and her visual acuity improved. However, during the subsequent treatment course, angle nodules were observed in the left eye, and the intraocular pressure (IOP) gradually increased. Although the angled nodules disappeared with topical corticosteroid treatment, the IOP did not reduce and became uncontrolled. Therefore, we performed trabeculotomy first, followed by trabeculectomy, after which the IOP decreased to approximately 10 mm Hg. Lessons: Unilateral granulomatous pan-uveitis and impending CRVO were observed in this patient. Several cases of Satoyoshi syndrome complicated by various autoimmune or immunological disorders have been reported. However, to the best of our knowledge, no reports of Satoyoshi syndrome presenting with uveitis or CRVO have been published. Physicians should consider uveitis as a complication of Satoyoshi syndrome.